(untitled) (Texas Journal of Medical Science, 2025)
Cardiac arrhythmias are disorders of heart rhythm caused by abnormalities in the generation or conduction n of electrical impulses . These conditions range from benign to life-threatening and can significantly impact patient morbidity and mortality . This article explores modern classification systems for arrhythmias , current diagnostic methods and recent advancements in treatment strategies , including pharmacological therapy , catheter ablation and implantable devices